Wątki polityczne w oskarżeniach kierowanych przeciwko biskupom w późnym cesarstwie rzymskim - Bralewski, Sławomir (Acta Universitatis Lodziensis. Folia Historica, 2000)
The Church, which since the time of Constantine the Great had participated in the political life of the Empire, clashed continually with institutions of the state. That is why a political accusations also appeared frequently in the charges put against clergymen. It is worth noticing that such charges were levelled not only by emperors and their officials but also bishops themselves. The emperors utilised the indictments as a means of eliminating from the life of the Church and state personages that stirred up trouble. It also happened, however, that it was the political misconduct which was the main reason for imperial hostility towards certain bishops, like John Chrysostom. However, in this case the charges brought against him, with one exception only, referred to entirely different matters and were formulated – as we can infer - so as not to harm the reputation of the imperial court. In order to receive imperial support, clergymen were eager to make use of political charges to avoid any official references to the doctrine of the Church and differences that split the Christians. The most frequent charges include questioning of imperial orders which concerned ecclesiastical issues, which frequently led to an organised or spontaneous rebellion. Other accusations concern high treason and embezzlement of the funds received from the emperor to conduct charity actions. The third most frequent charges accuse the clergymen of support given to the emperor’s political enemies.